Twenty years of Dipterology through the pages of Zootaxa - Whitmore, Daniel; Gaimari, Stephen D.; Nihei, Silvio S.; Evenhuis, Neal L.; Kurina, Olavi; Borkent, Christopher J.; Sinclair, Bradley J.; O’hara, James E.; Zhang, Zhi-Qiang; Moulton, John K.; Ribeiro, Guilherme Cunha; Bickel, Daniel J.; et al. (Zootaxa, 2021)
We present a summary and analysis of the Diptera-related information published in Zootaxa from 2001 to 2020, with a focus on taxonomic papers. Altogether, 2,527 papers on Diptera were published, including 2,032 taxonomic papers and 1,931 papers containing new nomenclatural acts, equivalent to 22% of all publications with new nomenclatural acts for Diptera. The new nomenclatural acts include 7,431 new species, 277 new genera, 2,003 new synonymies, and 1,617 new combinations. A breakdown by family of new taxa and new replacement names proposed in the journal during the last two decades is provided, together with a comparison of Zootaxa’s output to that of all other taxonomic publications on Diptera. Our results show that the journal has contributed to 20% of all biodiversity discovery in this megadiverse insect order over the last 20 years, and to about 31% in the last decade.